2022
DOI: 10.9778/cmajo.20210234
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Ontario health system leaders on single-entry models for managing the COVID-19 elective surgery backlog: an interpretive descriptive study

Abstract: Background:The COVID-19 pandemic has exacerbated pre-existing challenges with respect to access to elective surgery across Canada, and a single-entry model (SEM) approach has been proposed as an equitable and efficient method to help manage the backlog. With Ontario's recent investment in centralized surgical wait-list management, we sought to understand the views of health system leaders on the role of SEMs in managing the elective surgery backlog.Methods: We used the qualitative method of interpretive descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Centralized referral systems designed to improve timely access to procedures have only recently been implemented in Ontario for hip and knee replacement and anorectal surgeries, and there is still a dearth of evidence as to whether these systems reduce gender-based biases in referrals. However, a recent qualitative study suggested such systems may be gaining acceptability in the current environment, as solutions are needed to address the surgical backlogs precipitated by SARS-CoV-2 infection …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Centralized referral systems designed to improve timely access to procedures have only recently been implemented in Ontario for hip and knee replacement and anorectal surgeries, and there is still a dearth of evidence as to whether these systems reduce gender-based biases in referrals. However, a recent qualitative study suggested such systems may be gaining acceptability in the current environment, as solutions are needed to address the surgical backlogs precipitated by SARS-CoV-2 infection …”
Section: Discussionmentioning
confidence: 99%
“…However, a recent qualitative study suggested such systems may be gaining acceptability in the current environment, as solutions are needed to address the surgical backlogs precipitated by SARS-CoV-2 infection. 32 …”
Section: Discussionmentioning
confidence: 99%
“…SEMs require an iterative process of quality improvement where feedback is provided by patients, referring health care providers, and those who treat these patients, and the centralized collection of patient and provider data helps to identify gaps in care. 10 The quasi-objective criteria of urgency and necessity in triaging patients within SEMs helps improve equity and access to treatment. 10 Previous research has highlighted patient and provider satisfaction after SEMs were implemented.…”
Section: Introductionmentioning
confidence: 99%
“… 10 The quasi-objective criteria of urgency and necessity in triaging patients within SEMs helps improve equity and access to treatment. 10 Previous research has highlighted patient and provider satisfaction after SEMs were implemented. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“… 15 , 17 , 19 As the pandemic evolved, research and recommendations focused more on guiding surgical recovery efforts. 5 , 21 - 23 However, anecdotal evidence suggests that there was no consensus or universally adopted approach for managing surgical care across Canada, and there has been little cross-jurisdictional interaction towards planning the way forward for surgical care in Canada. This may be a missed opportunity to learn from successes and challenges during the COVID-19 pandemic and in other times of constrained healthcare resources.…”
Section: Introductionmentioning
confidence: 99%